EXPERIMENTAL STUDY AND PERFORMANCE OF PV SYSTEM AND PEDAL POWER WITH GRID - Verma, Priyanka Suman; Sharma, A.K. (International Journal of Research -GRANTHAALAYAH, 2016)
A solar cell is essential a PN junction with a large surface area. The N-type material is kept thin to allow light to pass through to the PN junction.Light travels in packets of energy called photons. The generation of electric current happens inside the depletion zone of the PN junction. The depletion region as explained previously with the diode is the area around the PN junction where the electrons from the N-type silicon, have diffused into the holes of the P-type material. 3.2.3- Pedal power- Some applications include pedal powered laptops, pedal powered grinders and pedal powered water wells. Some third world development projects currently transform used bicycles into pedal powered tools for sustainable development. The articles on this page are about the many wonderful applications for pedal power technology